Developments in undergraduate wood science education at Stellenbosch University, South Africa - Rypstra, Tim (Maderas. Ciencia y Tecnología, 2025)
In South Africa, Stellenbosch University (SU) is the designated provider of Bachelor, Master and Doctorate level qualifications in Forestry and Wood Products Science. SU provides educational programs to both mechanical (sawmilling, preservation, composite products, furniture, etc.) and the chemical (pulp & paper) processing sectors. To ensure academic quality, SU regularly has her academic programs assessed externally. In 2000, several changes to the then existing 4 year B.Sc. Wood Science program were recommended. A restructured SU undergraduate program, similar to the B.Sc. Wood Products Processing program at the University of British Columbia (UBC), Vancouver, Canada, was consequently introduced in 2003. That same year, to provide more support to this effort, a partnership between UBC, SU and the Nelson Mandela Metropolitan University, the SA institution responsible for the National Diploma and Bachelor of Technology degrees in similar subjects, was established. The objective was to develop and deliver successful tertiary programs in value-added wood product processing education for South Africa and later, for other African countries as well. A Wood Products Processing Education Project, implemented in 2004 and running until mid 2010, funded by the respective partner institutions and the Canadian International Development Agency (CIDA) through the University Partnership in Cooperation and Development Program, was established. In addition to curriculum developments based on the UBC model, module content was modified to address relevant South African conditions. To make modules accessible to part-time students and members of industry off-campus, conversion of several Wood Products Science modules into e-learning format was implemented. A concise overview of Wood Science education at Stellenbosch University is given and the implementation and progress of the CIDA project at SU is briefly discussed. Solutions to the educational needs of the SA pulp & paper sector are also highlighted.